2008
DOI: 10.1074/jbc.m709446200
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of BRMS1-ARID4A Interaction Modify Gene Expression but Still Suppress Metastasis in Human Breast Cancer Cells

Abstract: The BRMS1 metastasis suppressor interacts with the protein AT-rich interactive domain 4A (ARID4A, RBBP1) as part of SIN3⅐histone deacetylase chromatin remodeling complexes. These transcriptional co-repressors regulate diverse cell phenotypes depending upon complex composition. To define BRMS1 complexes and their roles in metastasis suppression, we generated BRMS1 mutants (BRMS1 mut ) and mapped ARID4A interactions. BRMS1L174D disrupted direct interaction with ARID4A in yeast two-hybrid genetic screens but reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 33 publications
1
100
0
Order By: Relevance
“…We propose that a model for BRMS1 dimerization based on the structure of the Sds3 dimerization domain is likely to be physiologically relevant. Indeed, previous genetic and biochemical studies have shown that BRMS1 could recruit ARID4A/B to the complex in a manner dependent on intact CC1 and CC2, raising the possibility that CC1 and CC2, which are in close proximity in the Sds3-based model for the dimer, form a recruiting platform for these types of interactions (37). However, it has been shown that Sds3 is unable to suppress metastasis in the absence of BRMS1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…We propose that a model for BRMS1 dimerization based on the structure of the Sds3 dimerization domain is likely to be physiologically relevant. Indeed, previous genetic and biochemical studies have shown that BRMS1 could recruit ARID4A/B to the complex in a manner dependent on intact CC1 and CC2, raising the possibility that CC1 and CC2, which are in close proximity in the Sds3-based model for the dimer, form a recruiting platform for these types of interactions (37). However, it has been shown that Sds3 is unable to suppress metastasis in the absence of BRMS1 (38).…”
Section: Discussionmentioning
confidence: 99%
“…40 µg of total protein was loaded onto a 10% SDS-PAGE gel and transferred to PVDF membrane. All membranes were blocked overnight at 4°C and immunoblotting was done with mouse anti-BRMS1 antibody (at 1:2,500) [27] or with mouse anti-β-actin antibody (1:30,000). Anti-mouse HRP conjugated secondary antibody was used for detection and blots were developed with SuperSignal enhanced chemiluminescence substrate (Pierce, Rockford, IL) and exposed using a Fuji LAS3000 imager.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…For Breast Cancer Metastasis Suppressor-1 (BRMS1), the clinical data reporting it to be a metastasis suppressor protein in breast cancer tumour samples is also conflicting (Kelly, Buggy et al 2005;Hicks, Yoder et al 2006;Lombardi, Di Cristofano et al 2007). Again, its role in mouse models is clearer, where higher expression in breast cancer xenografts clearly resulted in reduced metastasis (Hedley, Vaidya et al 2008;Hurst, Xie et al 2008;Phadke, Vaidya et al 2008). The stage at which BRMS1 suppresses metastasis is less clear, as it appears to affect a number of steps in the process of metastasis (Stafford, Vaidya et al 2008).…”
Section: Metastasis Suppressor Genesmentioning
confidence: 99%